"It's such a vicious cycle": Narrative accounts of the sportsperson with epilepsy. (May 2016) - Collard, Sarah S.; Marlow, Caroline
Abstract: Objectives: There is an abundance of quantitative and medical research promoting the benefits of exercise for people with epilepsy. However, the psychosocial barriers and benefits of exercising for the sportsperson/people with epilepsy (SWE) are absent. This research aims to present the narratives of SWE over time and as a result, develop further understanding of the psychosocial impact of exercising with epilepsy. Method: A holistic-content and structural narrative analysis were used to explore the exercise experiences of three SWE over the course of one year. A creative non-fictional technique was used to present first person narratives, therefore providing the SWE's voice for the reader. Results: Narratives of 'vicious cycle' and 'roller coaster' presented complex and multi-thematic storied forms, with time and the hidden nature of epilepsy having a strong impact on narrative formation. Vicious cycle presented the cycle of desiring to exercise, but prevented from exercising because of uncontrolled seizures. This resulted in frustration and feelings of a lack of control, which subsequently increased the desire to exercise and created a cycle with no clear end. Roller coaster presented the constant psychosocial and physical undulations that epilepsy can create for a SWE over time. Conclusion: These narratives reveal that exercising with epilepsy has a constant and on-going positive and negative impact on the life of SWE. However, these narratives also show that it may be through the process of acceptance of their body's limitations that a healthier mental and physical state may result for the SWE. Highlights: Narrative inquiry over time of the sportsperson with epilepsy. Vicious cycle is the cyclical narrative of exercising with uncontrolled seizures. Roller coaster shows the emotional undulations of exercising with epilepsy. Hidden aspect of epilepsy impacts emotional reaction to exercise limitations.